How development projects persist : everyday negotiations with Guatemalan NGOs - Beck, Erin, 1982- (Duke University Press, 2017)
Erin Beck examines microfinance NGOs working with poor, rural women in Guatemala to show how these women creatively and strategically use the NGOs to their own benefit in ways that do not necessarily match the goals of the NGOs, demonstrating that development projects are often transformed and persist in unexpected ways.